The Management of zakat distribution on asnaf fisabillah by Pusat Zakat UiTM Puncak Alam / Ariffahmi Samsuri - Samsuri, Ariffahmi (2019)
The management of zakat money in a trustworthy and systematic manner is important and must be taken seriously by management agency or institution involved. This study was conducted at Bahagian Zakat, Sedekah dan Wakaf (Zakat, Charity and Waqf divisions), UiTM with the objective to refine the concept of zakat distribution among asnaf fisabillah in UiTM and identify their criteria as well. This study used a qualitative method which is interview on informer who are directly involved in managing this zakat fund. The interview data were analyzed to obtain the informations required. The results of this study found that the Bahagian Zakat, Sedekah dan Wakaf (Zakat, Charity and Waqf divisions) UiTM can effectively identifying the asnafs who are entitled zakat until the distribution level of the money that needed by asnaf in UITM.